COVID-19: Malaysia's fight against this deadly virus - Ke-Yan Loo; Vengadesh Letchumanan (Progress in Microbes and Molecular Biology)
Malaysians are facing the biggest challenge in 2021 - the rise in COVID-19 cases and its variant of concern (VOC) strains. The scale and impact of this coronavirus disease are unimaginable, scary, and full of sorrows. Many lost their loved ones, relatives, friends, and children are becoming orphaned overnight. Now our only hope is on the available vaccines to control this deadly virus infection. When this Review article was in press, over 170 million confirmed cases with 3.5 million deaths were reported worldwide. Malaysia is dealing with spikes in the number and severity of new cases. A record toll of new cases and fatalities for consecutive weeks has pushed Malaysia's total cases to a soaring 500,000 confirmed cases with 2300 deaths – the third highest in Southeast Asia behind Indonesia and the Philippines. The healthcare system in Malaysia is currently under heavy pressure to control the disease as the number of confirmed cases is rising exponentially. A National COVID-19 Immunization Program was launched in February 2021 in the hope of providing immunity to 80% of the population in Malaysia and achieve herd immunity. This review discusses the alarming COVID-19 situation in Malaysia, the management strategies, and the vaccinations program.